2004
DOI: 10.1080/13607860410001725063
|View full text |Cite
|
Sign up to set email alerts
|

Are the Health of the nation outcome scales (HoNOS) useful for measuring outcomes in older people'smental health services?

Abstract: The Health of the Nation Outcome Scales (HoNOS) were developed to provide a single index in order to enable the government target 'to improve significantly the health and social functioning of mentally ill people' to be quantified. They were intended to be applicable to all adults (including older people), across a wide range of settings so that services in different localities could be compared and changes both within individuals and within services could be measured. In 1999 the HoNOS65+ was launched with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Anecdotally, some clinicians question the psychometric soundness of the instruments, and argue that they do not have good clinical utility [ 7 ]. With the exception of a specific review of the applicability of the HoNOS and the HoNOS65+ for older people [ 8 ], there has been no comprehensive review of these instruments that can inform this debate. The current paper fills this gap, by appraising the psychometric properties of each.…”
mentioning
confidence: 99%
“…Anecdotally, some clinicians question the psychometric soundness of the instruments, and argue that they do not have good clinical utility [ 7 ]. With the exception of a specific review of the applicability of the HoNOS and the HoNOS65+ for older people [ 8 ], there has been no comprehensive review of these instruments that can inform this debate. The current paper fills this gap, by appraising the psychometric properties of each.…”
mentioning
confidence: 99%
“…The HoNOS family of measures is most widely used in UK and Australia and the HoNOS65+ is considered as one of the six most commonly used assessment scales in old age psychiatry services providing key material results for shaping the provision of psychiatric services for older people [38]. Previous contributions showed that the HoNOS65+ is an acceptable clinical outcome measure for use in the evaluation of mental health services for elderly persons [15,37,39]. Moreover, earlier studies have pointed to the ability of the HoNOS65+ to discriminate between patients with dementia and those with functional psychiatric disorders [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…De HoNOS is het meest gebruikte beoordelingsinstrument in Engeland en Australië en blijkt gevoelig voor veranderingen in het toestandsbeeld bij de cliënten. 4 Vooral voor bepaalde doelgroepen (zoals mensen met een psychose, kinderen, ouderen), die misschien niet altijd goed in staat zijn de vragenlijst zelf in te vullen, is de HoNOS een ge-schikt instrument om in Routine Outcome Assessment te worden opgenomen. De HoNOS wordt ook in Nederland al veel gebruikt, vooral in de langdurende zorg.…”
Section: Inleidingunclassified